New data on intermediate host of fasciola in Vietnam - Doanh, Pham Ngoc; Hien, Hoang Van; Duc, Nguyen Van; Cam Thach, Dang Thi (Academia Journal of Biology, 2012)
Previous studies reported two Lymnaea snail species (L. viridis and L. swinhoei) as the intermediate hosts of Fasciola spp. in Vietnam. In this study, we investigated in 32 communes of 9 provinces representing for 3 areas of Vietnam for Fasciola cercaria in Lymnaea spp. snails. We collected three Lymnaea species, L. viridis, L. swinhoei and Lymnaea sp.. Of these, L. viridis is smallest in size (2-10 mm in length) and mainly living in rice fields with a little water. In contrast, L. swinhoei is large (5-20 mm) with the larger mouth, mainly found in ponds, lakes or rivers; an unidentified Lymnaea sp. (5-20 mm) has relatively slender and longer whorl, and thrive in clear stagnant or slow-moving water rivers or canals. A total of 43,910 individual snails, including: 33,510 L. viridis, 9,400 L. swinhoei and 1,000 Lymnaea sp. were examined. Fasciola cercariae were found only in L. viridis in some sites at very low infection rates (0.06-4.0%). The susceptibility of snails to Fasciola larvae and the role of Fasciola transmission of Lymnaea spp. in Vietnam should be explored more extensively in future.